Doppler Estimation Based on Frequency Average and Remodulation for Underwater Acoustic Communication - Chan-Ho Hwang; Ki-Man Kim; Seung-Yong Chun; Sang-Kook Lee (International Journal of Distributed Sensor Networks)
Underwater acoustic communication channel is time varying and has Doppler effect due to wind, sea surface roughness, and platform motion. We have to recognize the changing channel state and apply it to communication technique for increasing transmission efficiency in the underwater acoustic channel. In this paper, we propose more reliable Doppler estimation method based on frequency average and remodulation. We conducted the simulation and sea trial to evaluate the performance of the proposed method. When the channel coding technique was not applied, the uncoded bit error rate performance of the proposed method was improved about maximum 50.3% compared with conventional method.